An exploration of the landscape of fundamental movement skills and strength development in UK professional football academies - Smothers, N.; Cropley, B.; Lloyd, R.; Oliver, J. (International Journal of Sports Science & Coaching, 2021)
The purpose of this study was to investigate the landscape of Fundamental Movement Skills (FMS) and strength development in professional football (soccer) academies in the UK. To achieve this, we interviewed 16 participants, whose primary responsibility was the physical development of youth players from a variety of Elite Player Performance Plan (EPPP) categorised academies. Following abductive analysis, we identified that whilst all participants acknowledged the importance of FMS and strength development for young football players, there was variance across EPPP categories relating to: (a) the time dedicated to developing FMS and strength; (b) the number, level of qualification, and utilisation of staff; and (c) the integration of the evidence informed practice into programme design and delivery. Although the key foci of academy strength and conditioning programmes generally prioritised injury reduction, performance improvement, and building a physical base for future development, the methods used to achieve these outcomes were varied. Finally, participants reported how relationships between support staff and technical coaching staff had a direct impact on the implementation of FMS and strength programmes. We have provided rich insights into a range of factors that may facilitate or hinder FMS and strength development within youth football players and thus helped to advance understanding of the practical implications of focusing on these key skills within athlete development programmes.